Krüppel-like Factor 4, a “Pluripotency Transcription Factor” Highly Expressed in Male Postmeiotic Germ Cells, Is Dispensable for Spermatogenesis in the Mouse - Godmann, Maren (2009)
Krüppel-like factor 4 (Klf4, GKLF) was originally characterized as a zinc finger transcription factor essential for terminal differentiation and cell lineage allocation of several cell types in the mouse. Mice lacking Klf4 die postnatally within hours due to impaired skin barrier function and subsequent dehydration. Recently, KLF4 was also used in cooperation with other transcription factors to reprogram differentiated cells to pluripotent embryonic stem cell-like cells. Moreover, involvement in oncogenesis was also ascribed to KLF4, which is aberrantly expressed in some types of tumors such as breast, gastric and colon cancer. We previously have shown that Klf4 is strongly expressed in postmeiotic germ cells of mouse and human testes suggesting a role for Klf4 also during spermiogenesis. In order to analyze its function we deleted Klf4 in germ cells using the Cre-loxP system. Homologous recombination of the Klf4 locus has been confirmed by genomic southern blotting and the absence of the protein in germ cells was demonstrated by western blotting and immunofluorescence. Despite its important roles in several significant biological settings, deletion of Klf4 in germ cells did not impair spermiogenesis. Histologically, the mutant testes appeared normal and the mice were fertile. In order to identify genes that were regulated by KLF4 in male germ cells we performed microarray analyses using a whole genome array. We identified many genes exhibiting changed expression in mutants even including the telomerase reverse transcriptase mRNA, which is a stem cell marker. However, in summary, the lack of KLF4 alone does not prevent complete spermatogenesis.